PROFITABILITY, LEVERAGE, COMPANY SIZE, AND NET WORKING CAPITAL'S IMPACT ON EARNINGS QUALITY - Nina Purnasari Purnasari; Lisbet Pasaribu; Vina Anasthasia Pasaribu (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study aims to understand the direction of Profitability, Leverage, Company Size and Net Working Capital on Earning Quality in food and beverage companies listed on the Indonesia Stock Exchange in 2017 - 2020. This researcher uses a population of 16 food and beverage companies listed on the Stock Exchange. Indonesia Stock Year 2017 - 2020. The method used in this study is a quantitative method. The data used is secondary data obtained from the official website www.idx.co.id. The research sample was taken using the purposive sampling method. The data investigation method used is the multiple linear regression method. The results showed that partially the effect of profitability, leverage, and net working capital had a positive but not significant effect on earnings quality. And Company Size has a positive and significant effect on Earnings Quality in food and beverage companies listed on the IDX in 2017 - 2020. Based on simultaneously Profitability, Leverage, Company Size and Net Working Capital have a positive and significant impact on Earning Quality in food and beverage companies that listed on the IDX in 2017-2020